Guatemala : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guatemala. (IMF Staff Country Reports; Country Report, 2021)
Guatemala has managed to keep infections and deaths moderate during the pandemic. The economic impact of COVID-19 has been mild given an early reopening of the economy, unprecedented policy support, and resilient remittances and exports. However, despite large-scale government interventions to support households, poverty and malnutrition have deteriorated following COVID-19 and the two major hurricanes battering Guatemala last November.